2020
DOI: 10.1037/cou0000386
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin as a biomarker of the formation of therapeutic alliance in psychotherapy and counseling psychology.

Abstract: The therapeutic alliance is one of the most consistent predictors of therapeutic change, including symptom reduction and improvement in wellbeing and quality of life, across a variety of mental health interventions. Yet, little is known about its biological mechanisms. Oxytocin (OT) has been suggested as a biological mechanism by which bonds are formed and strengthened across species. This article is intended to demonstrate the potential of OT as a biomarker of therapeutic change in psychotherapy and counselin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 107 publications
(149 reference statements)
1
43
0
Order By: Relevance
“…On the other hand, oxytocin administration was also found to enhance therapeutic response in hypnotic-based settings (Bryant et al, 2012), and recent studies have also demonstrated that oxytocin synchronization predicted better therapeutic outcome (Zilcha-Mano et al, 2020). Oxytocin has also been suggested to exert effects on synchronization phenomena in psychotherapy settings.…”
Section: Physiological Synchronization and Oxytocin In Psychotherapy Settingsmentioning
confidence: 99%
“…On the other hand, oxytocin administration was also found to enhance therapeutic response in hypnotic-based settings (Bryant et al, 2012), and recent studies have also demonstrated that oxytocin synchronization predicted better therapeutic outcome (Zilcha-Mano et al, 2020). Oxytocin has also been suggested to exert effects on synchronization phenomena in psychotherapy settings.…”
Section: Physiological Synchronization and Oxytocin In Psychotherapy Settingsmentioning
confidence: 99%
“…Considering their relative scarcity, the study adds to a burgeoning field of research that attempts to exploit biological markers as an additional avenue towards our understanding of in-session therapeutic dynamics [ 41 , 42 , 43 , 44 ]. The general importance of a holistic approach towards illness has repeatedly been highlighted, and many are the arguments supporting a biopsychosocial approach to mental disorders [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…This trial also found positive effects of oxytocin on aspects of group cohesion ( 19 ) and physiological synchrony ( 21 ); although oxytocin had no significant effect on methamphetamine use or craving after 6 weeks of treatment. Of note, endogenous oxytocin has been nominated as a possible biomarker for therapeutic alliance ( 22 ); and—regardless of the therapeutic modality—the strength of the therapeutic alliance consistently predicts addiction treatment engagement and retention as well as long-term relapse ( 7 , 23 ). Thus, it is important that we gain a better understanding of the relationship between oxytocin and therapeutic alliance, particularly among individuals with SUDs in controlled therapeutic environments ( 24 , 25 ).…”
Section: Introductionmentioning
confidence: 99%